Analisis Tentang Sistem Peradilan Agama Di Indonesia - -, Domiri (Jurnal Hukum & Pembangunan, 2016)
Religious Court serves as the judicial system in Indonesia, in addition it is also a subsystem of the Indonesian judicial system. The Indonesian judicial system is composed of several subsystems, such as, Religious Court, Commercial Court, Military Court, and the Administrative Court. As a judicial system, the Religious Court has several sub-systems or component. Its components are: first, the law itself, which includes procedural and substantive law. Secondly, the apparatus of the court, including judges, clerks, and bailiffs. Each of these components has their own duty and function.. The law serves as the guideline for all the officials of the Religious Court in carrying out their duties and functions. The judge assigned to make a judgement, to watch, to listen, to examine, and to decide the appointed casse. The Clerk is charged to record the proceedings and executes the court decision/execution. The Bailiff’s duty is to execute the commands of Chairman and execute seizure on the orders of Chief of the Court. All these components work synergistically in achieving a goal that is the law and justice are regarded as the most supreme power.